The Effect of Soy Milk and Mung Bean Juice Consumption on Increasing Breast Milk Production in Breastfeeding Mothers - Sunaryati, Aina; Solihah, Ahda Roudhotun; Mulyawati, Elin; Budiarti, Evita; Chasanah, Maranis (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The Banten Province Central Bureau of Statistics in 2023 recorded that the exclusive breastfeeding rate was only 72.62%. In Indonesia, 31.36% of 73.94% of children fall ill due to not receiving exclusive breastfeeding.This study aims to evaluate the effect of soy milk and mung bean juice consumption on breast milk production in breastfeeding mothers at Puskesmas Saketi in 2024. This study provides treatment to breastfeeding mothers by giving them soy milk and green bean juice, 250 ml each per day for 7 days. A quasi-experimental study with a One Group Pre and Post Test Design. The sampling technique used in this study was Saturation Sampling, where the entire population in this study was used as the sample, totaling 32 people, with a paired sample t-test. There was an effect of consuming soy milk and mung bean juice on increasing breast milk production in breastfeeding mothers at Puskesmas Saketi Pandeglang in 2024, with a p-value of 0.000 (p < 0.05) in the Paired Sample Test. Conclusion: The average breast milk production before consuming soy milk and green bean extract was 81.72 ml, while the average breast milk production after consuming soy milk and green bean extract for seven days increased to 122.50 ml.